Strategi Pengendalian Inflasi Daerah Berbasis Komoditas Pangan di Kabupaten Sukabumi: Analisis Indeks Perkembangan Harga (IPH) dan Dinamika Inflasi Tahun 2025–2026 - chefy, Yana Chefiana (Jurnal Agriust, 2026)
Inflation is an important indicator in maintaining regional economic stability because it affects people's purchasing power and household welfare. Sukabumi Regency, as a non-CPI region, uses the Price Development Index (IPH) as an inflation proxy to monitor changes in strategic commodity prices. This study aims to analyze the development of inflation and the IPH in Sukabumi Regency and formulate a regional inflation control strategy. The method used is descriptive research with a secondary data analysis approach sourced from the report of the Regional Inflation Control Team (TPID) of Sukabumi Regency for 2025–2026. The results show that inflation in West Java in December 2025 reached 2.63 percent (year-on-year), while Sukabumi City experienced inflation of 3.14 percent. Food commodities such as red chilies, cayenne peppers, shallots, rice, broiler chicken, and broiler chicken eggs were the main contributors to inflation. In the second week of January 2026, the IPH in Sukabumi Regency was recorded at -2.0 percent, lower than the IPH in West Java at -1.27 percent. This decline was influenced by falling prices for red chilies, cayenne peppers, and shallots. Inflation control strategies need to focus on price stabilization, strengthening food production, strengthening food stocks, improving trade infrastructure, and strengthening inter-regional cooperation